2013
DOI: 10.1002/pits.21702
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention of Teachers, School Psychologists, and Counselors to Intervene and Prevent Harassment of LGBTQ Youth

Abstract: A national sample of educators were surveyed to identity the attitudes, beliefs, school culture, and perceived barriers that would predict whether educators would intervene to stop bias and harassment directed at lesbian, gay, bisexual, transgendered, and questioning (LGBTQ) youth in schools. The survey questionnaire was organized according to the theory of planned behavior (TpB), a theoretical model linking attitudes to behavior. A sample of 968 teachers, school psychologists, and school counselors participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…The findings show that homonegative teachers are less inclined to discuss sexual diversity in the classroom (Sears, 1992) or intervene when homophobic acts occur (McCabe, Rubinson, Dragowski, & Elizalde-Utnisk, 2013) and are more likely to value strict adherence to gender norms (Blount, 2000;Cahill & Adams, 1997). According to Sears (1992), teachers know how to act to foster the well-being of their LGBQ students, but many of the educators' actions may be inhibited by significant personal prejudice, ignorance, or concern.…”
Section: Homonegative Attitudesmentioning
confidence: 86%
“…The findings show that homonegative teachers are less inclined to discuss sexual diversity in the classroom (Sears, 1992) or intervene when homophobic acts occur (McCabe, Rubinson, Dragowski, & Elizalde-Utnisk, 2013) and are more likely to value strict adherence to gender norms (Blount, 2000;Cahill & Adams, 1997). According to Sears (1992), teachers know how to act to foster the well-being of their LGBQ students, but many of the educators' actions may be inhibited by significant personal prejudice, ignorance, or concern.…”
Section: Homonegative Attitudesmentioning
confidence: 86%
“…reactions to homophobic bullying comprise the contextual variables, as it has been shown that they 25" play a significant role in shaping the manner in which school staff manage homophobic bullying 26" 6" " (Collier et al, 2015;McCabe et al 2013;Novick & Isaacs, 2010). Pursuing this goal would allow 1" us to clarify the specific contribution of the individual and contextual factors as unique predictors of 2" staff reactions to homophobic bullying in terms of legitimization of or intervention to counteract 3" homophobic bullying episodes.…”
Section: "mentioning
confidence: 99%
“…individual together with contextual factors and school staff reactions to homophobic bullying were 6" carried out in the Netherlands and the United States (Collier et al, 2015;McCabe et al 2013), while 7" no research on this issue has yet been carried out in the Italian context. A recent Eurobarometer 8" survey in the European Union has shown that the Italian context is characterized by high levels of 9" negative attitudes toward LG individuals (European Commission, 2015; see also, Baiocco, Nardelli, 10" Pezzuti, & Lingiardi, 2013;Lingiardi, Falanga, & D'Augelli, 2005), and a national survey has 11"…”
Section: "mentioning
confidence: 99%
See 1 more Smart Citation
“…When attitudes are strong and the subjective norm is favorable, the perceived behavioral control becomes powerful, thus increasing an individual's engagement in a behavior and the likelihood that the individual intends to perform the behavior. In our previous work (McCabe, Rubinson, Dragowski, & Elizalde‐Utnick, ), we validated a TpB model predicting educators’ reported intention to intervene in cases of LGBTQ BH in schools, and this framework was applied in this study.…”
mentioning
confidence: 99%